The influence of the CSR Committee in firm’s financial and non-financial performance: Evidence from France, Germany, and the UK - Lopes, A.I.; Jorge, I. (2021 JIAR Conference, 2021)
The CSR committee is a corporate governance mechanism used by companies to encourage and develop corporate social responsibility, promoting and complying with a CSR oriented strategy. This study is an analysis of how a CSR committee can influence firms’ performance, comprising companies from the higher European countries by GDP. In the first approach, it is analyzed the influence of the CSR committee on financial and non-financial performance. Then, the moderate role of environmentally sensitive industries, and the influence of the implementation of the Directive 2014/95/EU, are analysed. The results show that the existence of a CSR committee is generally positively (negatively) associated with non-financial (financial)performance by the company. While this relationship is not statistically different for firms with CSR Committee belonging to an environmentally sensitive industry, findings suggest that the effectiveness of the Directive 2014/95/EU turns the relationship between CSR Committee and financial performance to positive